Morphosyntactic transference of Aymara in Spanish - Romero Sihuayro, Miguel Angel (2018)
This research study uses a descriptive type of qualitative approach, focused on describing the morphosyntactic transference of Aymarain Spanish among students of the fifth grade in the Primary School N° 70274 Challapampa –Copani -Yunguyo –Puno, 2017. The sample was made up of 12 students from the only fifth grade classroom, chosen by intentional nonprobabilistic sampling. Two instruments were applied to collect the data: The first one called "Linguistic Competency Performance Record in the Production of Written Texts in Spanish" and the second "Linguistic Competency Performance Report in the Production of Spanish Oral Texts", the data were analyzed with the Corder Contrastive Analysis technique. The result of the research show that the contact of languages which characterizes the C.P. Challapampa, gives rise to linguistic transference phenomena, especially at the morphosyntactic level where students make use of the morphosyntactic structure of Aymara S + O + V to write in Spanish, which is incorrect, since the structure of Spanish is S + V + O; frequent use of expressions such as hemosand taba; loan words from the Aymara language such as the expressions waka, awatiw; and finally the replacement of the vowel /e/ with /i/.